Re-Conceptualizing Vertical Subdivision Development for Sustainable, Affordable Housing Delivery - Nathan Tetteh; Masa Noguchi (Encyclopedia, 2024)
Research on sustainable, affordable housing is evolving. Yet, its conceptual efficacy in light of the changing needs of today’s cities and targeted low-to-middle-income households remains unknown. In today’s rapidly urbanizing world, understanding the conceptual relevance and importance of land use planning tools such as vertical subdivision to the delivery of sustainable housing is tenable. In response to this knowledge gap, this entry inquires, how can the delivery of affordable housing be configured in a manner that leverages the potential of a redefined vertical subdivision development to optimize densities and ensure that housing affordability is sustainable? Here, this entry re-defines vertical subdivision development as a housing planning and design tool that allows for the segregation of air spaces into individual volumetric land parcels that mimic the environmental features of the land-on-ground, such that housing construction within such volumetric spaces is a function of the contextually relevant needs of occupants. This entry demonstrates a paradigm shift from existing housing infrastructure planning models and narratives to one that responds to and addresses all three dimensions of sustainability: economic (sustainable affordability), environmental (sustainable densities), and social (occupant wellness) in the housing infrastructure planning and delivery process.